Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 350,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

It's certainly possible, using either or both statements, that p = q = pq = 1. It's also possible that p = q = pq = 0. So the answer is E. _________________

Nov 2011: After years of development, I am now making my advanced Quant books and high-level problem sets available for sale. Contact me at ianstewartgmat at gmail.com for details.

You forgot to consider whether p or q are 0, in which case you'd be dividing by 0 (which is undefined). If it's not stated that the variable can't be 0, move the variables to one side and factor. _________________

Statement 1- pqp = p p (pq-1)=0 It means p=0 or pq=1 Not sufficient

Statement 2- qpq = q q (pq-1)=0 It means q=0 or pq=1 Not sufficient

Statement 1 & 2- Combining both statements we get p^3q^2 - p = 0 p(p^2q^2 - 1) = 0 p (pq-1)(pq+1) = 0 p=0 or pq=1 or pq=-1 Not sufficient Answer E _________________

If you like my Question/Explanation or the contribution, Kindly appreciate by pressing KUDOS. Kudos always maximizes GMATCLUB worth-Game Theory

If you have any question regarding my post, kindly pm me or else I won't be able to reply

yes but if (1) gives us PQ= 1 as a possible conclusion, and so does (2), then cant we conclude that PQ=1 ?

That's not correct always and for the same reason i combined both the statements.

Hey can you please explain when to combine the statements and when not to ? I was under the impression that for such questions, one needs to look at the common solution from both the qquestions to arrive at the answer. If you could explain when to use these two approaches, it would help.

yes but if (1) gives us PQ= 1 as a possible conclusion, and so does (2), then cant we conclude that PQ=1 ?

That's not correct always and for the same reason i combined both the statements.

Hey can you please explain when to combine the statements and when not to ? I was under the impression that for such questions, one needs to look at the common solution from both the qquestions to arrive at the answer. If you could explain when to use these two approaches, it would help.

Thanks !

Notice that p=0 from the first statement does not exclude q being 0 too and similarly q=0 from the second statement does not exclude p being 0 too.

Is pq = 1?

(1) pqp = p --> p(pq-1)=0 --> either p=0 and q=(any number), including 0 so in this case pq=0 not 1 or pq=1. Not sufficient.

(2) qpq = q --> q(pq-1)=0 --> either q=0 and p=(any number), including 0 so in this case pq=0 not 1 or pq=1. Not sufficient.

(1)+(2) When combined we have that either p=q=0 or pq=1. Not sufficient.

Answer: E.

When we consider two statements together we should take the values which satisfy both statements. For this question pq=1 satisfies both statement, but p=q=0 also satisfies both statements. So what you call "common solution" for this question is: pq=1 OR pq=0\neq{1}.

Re: Is pq = 1? (1) pqp = p (2) qpq = q [#permalink]
04 Oct 2013, 00:18

Expert's post

suk1234 wrote:

DFG5150 wrote:

Is pq = 1?

(1) pqp = p

(2) qpq = q

This is how I approached the question; if anyone can kindly point out my flaw. The question is asking pq=1

or p=1/q or q=1/p

Meaning are p and q reciprocal?. Yes/No

Statement 1 pqp=p p^2q=p q=p/p^2 q=1/p so Sufficient

Statement 2

qpq=q q^2p=q p=q/q^2 p=1/q so Sufficient

Therefore the answer is C

If you say that each statement is sufficient, then you mean that the answer should be D, not C, right?

Now, the problem in your solution is that you cannot reduce pqp=p by p to get pq=1. This is because p can be zero and division be zero is not allowed.

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

So when you divide by p you assume, with no ground for it, that p does not equal to zero thus exclude a possible solution. Notice that p=0 and pq=1 both satisfy pqp=p.

Re: Is pq = 1? (1) pqp = p (2) qpq = q [#permalink]
04 Oct 2013, 00:36

Bunuel wrote:

suk1234 wrote:

DFG5150 wrote:

Is pq = 1?

(1) pqp = p

(2) qpq = q

This is how I approached the question; if anyone can kindly point out my flaw. The question is asking pq=1

or p=1/q or q=1/p

Meaning are p and q reciprocal?. Yes/No

Statement 1 pqp=p p^2q=p q=p/p^2 q=1/p so Sufficient

Statement 2

qpq=q q^2p=q p=q/q^2 p=1/q so Sufficient

Therefore the answer is C

If you say that each statement is sufficient, then you mean that the answer should be D, not C, right?

Now, the problem in your solution is that you cannot reduce pqp=p by p to get pq=1. This is because p can be zero and division be zero is not allowed.

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

So when you divide by p you assume, with no ground for it, that p does not equal to zero thus exclude a possible solution. Notice that p=0 and pq=1 both satisfy pqp=p.

The same logic applies to the second statement.

Hope it helps.

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

Yeaps! got it now. Thanks for the reply, it's very helpful. And thanks for that important bit of information.

Re: Is pq = 1? (1) pqp = p (2) qpq = q [#permalink]
04 Oct 2013, 01:02

Bunuel wrote:

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

This is a very important rule. Thanks bunnel. _________________

I'm telling this because you don't get it. You think you get it which is not the same as actually getting it. Get it?

gmatclubot

Re: Is pq = 1? (1) pqp = p (2) qpq = q
[#permalink]
04 Oct 2013, 01:02

I´ve done an interview at Accepted.com quite a while ago and if any of you are interested, here is the link . I´m through my preparation of my second...

It’s here. Internship season. The key is on searching and applying for the jobs that you feel confident working on, not doing something out of pressure. Rotman has...